Identifikasi Kesulitan Guru Dalam Melaksanakan Pembelajaran Kurikulum 2013 (Studi Kasus SMP Negeri 051 Bengkulu Utara) - Widiastuti, Eny (JURNAL ILMU PENDIDIKAN, 2022)
The learning process in the 2013 curriculum was carried out using a scientific approach. One of the requirements for the realization of learning using the 2013 curriculum is the existence of a paradigm shift in the teacher's learning process. This study aims to identify the difficulties of science teachers in implementing 2013 curriculum learning in SMP Negeri 051 North Bengkulu. Data collection techniques in the form of RPP documentation, observation of the implementation of learning and interviews with science teachers in 051 Bengkulu Utara Public Middle School. The data obtained were in the form of descriptive data on the difficulties of science teachers in implementing curriculum learning in 2013. The results showed that the difficulties faced by teachers in preparing Learning Implementation Plans were that teachers had difficulty in preparing appropriate learning objectives (37.5%), choosing appropriate teaching materials ( 12.5%), choose and use learning resources optimally (25%), and choose the appropriate learning method/model (50%), while the difficulties faced by teachers in implementing learning using the 2013 curriculum are teachers having difficulty in apperception, motivation, and learning objectives (47.92%), mastering learning materials (37.50%), conducting assessment activities and learning outcomes appropriately (47.91%), and implementing steps in closing lessons (50%).